2015
DOI: 10.1002/cncr.29572
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of germline BRCA mutation in patients with ER low‐positive/PR low‐positive/HER‐2 neu negative tumors

Abstract: Purpose 2015 NCCN guidelines recommend genetic counseling and germline BRCA mutation testing be offered to women under age 60 with triple negative breast cancer (TNBC). As a result of the 2010 ASCO/CAP guidelines in breast cancer, patients with breast cancers that are ER or PR low-positive (1–9% on immunohistochemistry) are no longer strictly considered to have TNBC and may not be referred for genetic counseling. However, the incidence of BRCA mutation in patients with hormone receptor (HR) low-positive breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…A potential pitfall of our study could be linked to the choice of a European definition of TNBC, considering a <10 % negativity threshold for the determination of the hormone receptor status. However, the fact that the exclusion of the 11 cases with HR values between 1 and 9 % did not change the multivariate analysis results, and the fact that recent biological studies showed a close biologic similarity between the <1 % HR and 1–9 % HR population [ 39 ], both strengthen our results.…”
Section: Discussionsupporting
confidence: 80%
“…A potential pitfall of our study could be linked to the choice of a European definition of TNBC, considering a <10 % negativity threshold for the determination of the hormone receptor status. However, the fact that the exclusion of the 11 cases with HR values between 1 and 9 % did not change the multivariate analysis results, and the fact that recent biological studies showed a close biologic similarity between the <1 % HR and 1–9 % HR population [ 39 ], both strengthen our results.…”
Section: Discussionsupporting
confidence: 80%
“…BRCA genes mutations, conferring increased risks for breast and high-grade serous cancer of the gynecological tract (fallopian tube, ovary and peritoneum), are closely associated with triple negative breast cancers (TNBC) (Foulkes, 2013;Sanford et al, 2015). Among the classifications of breast cancer, TNBC, manifested as early recurrence and poor survival, does not express estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2).…”
Section: Discussionmentioning
confidence: 99%
“…Among the classifications of breast cancer, TNBC, manifested as early recurrence and poor survival, does not express estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Among patients with TNBC, the incidence of BRCA1/2 mutation is estimated to range from 11-37% (Sanford et al, 2015;Young et al, 2009). TNBC accounts for about 70% and 16-23% of BRCA1 and BRCA2 mutation carriers, respectively (Stevens & Couch, 2013), suggesting that TNBC is also inextricably linked to germline mutation in this breast cancer susceptibility gene.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the association between the triple negative phenotype is more consistent in BRCA1 gene mutations than in BRCA2 ones 11 . A study conducted in a population consisting of 314 patients with triple negative breast cancer demonstrates this difference 11 : considering only patients with estrogen receptor (ER) and progesterone (PR) expression lower than 1%, the prevalence of BRCA1 mutations was 30%, whereas in BRCA2 it was 7% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the association between the triple negative phenotype is more consistent in BRCA1 gene mutations than in BRCA2 ones 11 . A study conducted in a population consisting of 314 patients with triple negative breast cancer demonstrates this difference 11 : considering only patients with estrogen receptor (ER) and progesterone (PR) expression lower than 1%, the prevalence of BRCA1 mutations was 30%, whereas in BRCA2 it was 7% 11 . Interestingly, these proportions were the same both for the group with ER and PR expressions of 1 to 9% and for less than 1%, which suggests that there are no biological differences between the two groups, with implications for the indication of tracing for HBOC and therapy 11 .…”
Section: Discussionmentioning
confidence: 99%